Isolasi, Pemurnian dan Karakterisasi Fitase Bacillus subtilis dari Holiwood Gresik - Leny Yuanita; Aline Puspita; Suzana Surodjo; Sri Hidayati; Farid Al Amin; Arif Budiman (The East Java Biological Society, 2010)
The aim of the research were isolation, purification and characterization of Bacillus subtilis phytase from Holiwood Gresik. The research was done in two stages; the first include enzyme isolation, precipitation with amonium sulphate, dialysis, gel filtration chromatography, SDS-PAGE analysis, while second determining optimum pH, optimum temperature, the effect of pH and temperature to enzim stability, the values of KM and Vmax Bacillus subtilis phytase from Holiwood Gresik. The first stage research design were One Shot Case Study and Post Test Only Control Group Design, while the second stage were Post Test Only Control Group Design and Factorial Design. The data being analyzed by one-way and two-way Anova. The results of research showed that Bacillus subtilis phytase has the molecular mass of 36.5 kDa, optimum pH at 6.5–7.0, optimum temperature at 41° C and it was found to be stable for 30 minute incubation at pH 7 or 30° C with 2% or 3% lost of its activity respectively. KM value was 0.62 mM and VMax 0.393 mmol/ml/minute.